Obtención de biopolímeros degradables a partir de glicerol y ácido cítrico extraído de la cáscara de naranja (2024)
"Due to the current environmental situation, it is necessary to seek strategies and alternatives to mitigate the environmental impact, specifically in the oceans since it is one of the main recipients of pollution, this is due to the large amount of plastic waste generated daily, affecting marine life and ecosystems, due to this, a solution aligned with environmental initiatives is proposed by developing a degradable biopolymer on a laboratory scale, based on the extraction of citric acid produced by the fermentation of orange peels with the microorganism Aspergillus Niger and glycerol that is produced in the biodiesel plant (Bio D located in the municipality of Facatativá). From the bibliographic review previously carried out, the favorable growth conditions of the microorganism were determined. The experimental results showed exponential growth at a temperature of 30 ° C, followed by this the extraction of citric acid from the orange peel was carried out starting from a solution of mycelium cake with distilled water, obtaining as a result 5.5 g / mL of citric acid. Having citric acid, biopolymers were produced after the polymerization reaction of citric acid from orange peel in a molar ratio of 1:3, compared with the polymerization reaction of pure citric acid in molar proportions of 1:1, 1:2 and 1:3 with glycerol from the plant. The synthesized biopolymers were characterized and the results obtained in moisture loss percentage tests were 2 to 11%, pH measurements ranged between 1.2 - 4.01, the relative density of these was 0.042-0.96 g/cm3 and the COD obtained results of 500 and 1500 mgO2/L. Finally, having these data, it was determined that a biopolymer with characteristics similar to polyurethane was obtained. "